Nutrient Uptake, Physiological Characters, And Yield Component Of Situbagendit Rice Variety On Nitrogen And Phosphor Dosage With Applications Of Vesicular Arbuscular Mycorrhiza On Rainfed Lowland Rice - Aziez, Achmad Fatchul; Wiyono; Supriyadi, Teguh (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2023)
Nutrient uptake, physiological characteristics and yield of rice situbagendit variety are influenced by differences in nitrogen and phosphorus doses with the application of vesicular arbuskular Mycorrhiza in rainfed lowland rice. The aim of this study was to determine the effect of nitrogen and phosphorus doses on situbagendit rice variety in rice fields that were given vesicular arbuskular Mycorrhiza. The research design used was Randomized Completely Block Design with 2 factors and 3 replications. The first factor was dosage nitrogen a.i. 0; .45; 90; 135 kg/ha. The second factor was 0; 25; 50; 75 kg/ha. The research was conducted in the rice field in the village of Demangan, Sambi, Boyolali, Central Java, Indonesia, 113 m above sea level. The results indicated that Nitrogen fertilization at 135 kg / ha increases nitrogen, phosphorus and potassium uptake and there is a correlation between nitrogen, phosphorus and potassium uptake. Starting with a nitrogen dose of 90 kg / ha increases the leaf area duration and there is a correlation between LAI, LAD and NAR. Phosphorus fertilization at a dose of 50 kg / ha increases grain weight per plot and per hectare and there is a correlation between the weight of 1000 grain, grain weight per plot and grain weight per hectare